Pengaruh Kecerdasan Emosional Terhadap Kinerja Karyawan Melalui Organizational Citizenship Behaviour pada Perusahaan Bersatu Sukses Group Surabaya - ARI PRATAMA, FERDIANSYAH (Jurnal Ilmu Manajemen (JIM), 2016)
This study aimed to analyze the effect of Emotional Intelligence on Employee Performance through Organizational Citizenship Behaviour. Sample used in this study is amounted to 52 employees Bersatu Sukses Group Surabaya Companies from various divisions specifically office staff and superintendent. Analsisis technique used in this study is Partial Least Square with the help of software SmartPLS3.0. The results of these studies show that emotional intelligence has positive influence on employee performance but not significant, Emotional Intelligence positive significant effect on Organizational Citizenship Behavior, Organizational Citizenship Behaviour positive significant effect on employee performance, and Emotional Intelligence positive significant effect on the Employee Performance through Organizational Citizenship Behaviour. Keywords: Emotional Intelligence, Organizational Citizenship Behavior, Employee Performance